2021
DOI: 10.1186/s12912-021-00759-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the experiences of working stressors and coping strategies associated with menstrual symptoms among nurses with shifting schedules: a Q methodology investigation

Abstract: Background The essence and workload of nursing can easily lead to burdens associated with female nurses’ menstrual symptoms, and consequently, result in decreased working performance. Without effective support this can lead to resignation due to maladaptation. This study adopted Q methodology to explore the experience of working stressors and coping strategies associated with menstrual symptoms among nurses with shifting schedules. Methods Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…and the Results of the Data. In order to ensure the smooth implementation of comprehensive student evaluation in the teaching management of university students work, it is necessary to use empirical analysis to complete the integration of all aspects of data [11,23].…”
Section: Discussion Of the Results Of The Different Dimensional Datamentioning
confidence: 99%
See 2 more Smart Citations
“…and the Results of the Data. In order to ensure the smooth implementation of comprehensive student evaluation in the teaching management of university students work, it is necessary to use empirical analysis to complete the integration of all aspects of data [11,23].…”
Section: Discussion Of the Results Of The Different Dimensional Datamentioning
confidence: 99%
“…Teaching staff could take responsibility for themselves and for their students and lead students to improve their overall quality and abilities, so that the students could establish the right learning philosophy. The students were able to strive to improve their professional knowledge ability to ensure that they could become useful talents in society [ 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiencing physical symptoms such as breast tenderness, headache, joint/muscle pain, bloating, weight gain, fatigue/lack of energy, experiencing anger or irritability (Hardy & Hunter, 2021). Menstrual symptoms interfere with cooperation with coworkers, professional functioning deficiency and stress due to symptom burden, diverse experiences without a clear pattern, adjusted self-management with and without drug use, and stress because of symptom burden and use of medication for self-management (Yu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It is crucial to facilitate access to treatment and coping behaviors at the appropriate time, depending on the severity of symptoms, rather than adopting coping behaviors when symptoms become more intense. Previous research has shown that women find discussing menstrual pain with their colleagues difficult and need workplace considerations and promotion of coping behaviors according to the severity of their symptoms and wishes [27]. Social support and flexible working arrangements, such as identifying women's symptoms and encouraging them to take time off to facilitate coping behavior, as well as promoting leave when needed and access to treatments, are important.…”
Section: Discussionmentioning
confidence: 99%